2018
DOI: 10.1002/ejhf.1372
|View full text |Cite
|
Sign up to set email alerts
|

Optimal haemodynamics during left ventricular assist device support are associated with reduced haemocompatibility‐related adverse events

Abstract: Aims Left ventricular assist device (LVAD) therapy improves the haemodynamics of advanced heart failure patients. However, it is unknown whether haemodynamic optimization improves haemocompatibility‐related adverse events (HRAEs). This study aimed to assess HRAEs in patients with optimized haemodynamics. Methods and results Eighty‐three outpatients [aged 61 (53–67) years, 50 male] underwent a haemodynamic ramp test at 253 (95–652) days after LVAD implantation, and 51 (61%) had optimized haemodynamics (defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 28 publications
0
78
0
Order By: Relevance
“…To our knowledge, this is the first study to address the impact of concomitant TVR on hemodynamics and LVAD performance. Hemodynamic optimization following LVAD implantation is associated with improved patient quality of life and a reduction in comorbidities . The hemodynamics of this study cohort improved significantly following LVAD implantation irrespective of concomitant TVR.…”
Section: Discussionmentioning
confidence: 69%
“…To our knowledge, this is the first study to address the impact of concomitant TVR on hemodynamics and LVAD performance. Hemodynamic optimization following LVAD implantation is associated with improved patient quality of life and a reduction in comorbidities . The hemodynamics of this study cohort improved significantly following LVAD implantation irrespective of concomitant TVR.…”
Section: Discussionmentioning
confidence: 69%
“…We have recently demonstrated that omega‐3, an unsaturated fatty acid, decreased the incidence of GIB during LVAD support, probably due to its suppressive effect on the development of arteriovenous malformation by inhibition of an angiogenesis‐related signal cascade . Considering that the treatment of bleeding, in general, has a negative impact on thrombotic events, we investigated in this study the impact of omega‐3 therapy on overall HRAEs including thrombotic events, as an expansion from our previous study, by using hemocompatibility score (HCS), which was originally proposed by Mehra and then used in the sub‐study of MOMENTUM 3 trial and the optimized hemodynamic comparison study …”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the protocol design of HEMO‐VAD pilot study proposed by Veenis and colleagues, in which the feasibility and implication of pulmonary artery pressure (PAP) guidance with CardioMEMS in patients with left ventricular assist device (LVAD) is prospectively investigated. Our team recently demonstrated the implications of hemodynamic optimization in LVAD patients, with the observed association of abnormal hemodynamics and heart failure (HF) readmissions along with hemocompatibility‐related adverse events …”
mentioning
confidence: 99%
“…However, the physiology of RVF during LVAD support is unique and complex. Increased right ventricular preload and anatomical changes experienced by the RV due to leftward shifting of the intraventricular septum both contribute maladaptive structure and function . Therefore, in patients with LVADs, RVF often exists in the absence of elevated left‐sided filling pressures, and as a result, PAP monitoring alone might not be an appropriate method to assess for the presence of RVF.…”
mentioning
confidence: 99%
See 1 more Smart Citation